2020
DOI: 10.1111/fcp.12596
|View full text |Cite
|
Sign up to set email alerts
|

Impact of interleukin‐6 on drug transporters and permeability in the hCMEC/D3 blood–brain barrier model

Abstract: The blood–brain barrier (BBB) is a highly selective membrane composed predominantly of brain capillary endothelial cells expressing drug efflux transporters that prevent substrates from accessing the brain. Inflammation is associated with central nervous system diseases and can impair BBB permeability via several mechanisms, including altered transporter and cell junction expression. This can modify the brain’s exposure to drugs. However, comprehensive genomic analysis of the impact of interleukin (IL)‐6, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…In the human brain endothelial cell line hCMEC/D3 cell line, in vitro model of the human blood–brain barrier (BBB), IL‐6 treatment slightly decreased the P‐gp mRNA level by 21% and had no significant impact on protein expression, and transporter activity 25 . Similar findings were observed in another study, IL‐6 treatment with hCMEC/D3 cell line reduced the P‐gp mRNA level by 43%, but only had mild modification of P‐gp transporter activity 26 …”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…In the human brain endothelial cell line hCMEC/D3 cell line, in vitro model of the human blood–brain barrier (BBB), IL‐6 treatment slightly decreased the P‐gp mRNA level by 21% and had no significant impact on protein expression, and transporter activity 25 . Similar findings were observed in another study, IL‐6 treatment with hCMEC/D3 cell line reduced the P‐gp mRNA level by 43%, but only had mild modification of P‐gp transporter activity 26 …”
Section: Introductionsupporting
confidence: 76%
“…reduced the P-gp mRNA level by 43%, but only had mild modification of P-gp transporter activity. 26 IFN-γ IFN-γ is a dimerized cytokine, secreted primarily by T helper cell type 1 (Th1) cells, CD8+ T cells, B cells, NK cells, and antigen presenting cells (monocytes, macrophages, and dendritic cells). 27 The monomer has a molecular weight of 20-25 kDa, and it is composed of a core of six-αhelix-bundle and an extended C-terminal region.…”
Section: Il-2mentioning
confidence: 99%
“…The human hCMEC/D3 cell line is derived from primary microvessel endothelial cells immortalised with SV40 and hTERT lentiviral transduction [228]. Due to its human origin, this cell line is widely used to study transporters and receptors for drug delivery to the brain [229][230][231][232]. An extensive characterisation of this cell line showed that the cells express endothelial and BBB markers and have a highly restricted permeability to molecules, which is closer to the physiological frame than animal immortalised brain endothelial cells [228].…”
mentioning
confidence: 99%
“…In addition, it is known that CYP3A and P-gp are both regulated by the same nuclear receptor, PXR [ 154 , 155 ]. Thus, it would be interesting to integrate all the pharmacokinetic actors in physiologically-based pharmacokinetic modeling (PBPK) to establish more complete in vitro–in vivo correlations, as suggested by Simon et al (2020) [ 156 ]. Conducting prospective and retrospective studies in humans could provide more evidence, by establishing for example, a link between the level of inflammatory markers such as CRP and a modulation of drug exposure [ 130 , 138 ].…”
Section: Discussionmentioning
confidence: 99%